Investigating the kinship between individuals deposited in exceptional Merovingian multiple burials through aDNA analysis: The case of Hérange burial 41 (Northeast France). (August 2018) - Deguilloux, Marie-France; Pemonge, Marie-Hélène; Rivollat, Maïté; Lefebvre, Arnaud
Abstract: In funerary studies, "multiple burials" that have received several individuals in the same grave at the same time naturally raise questions concerning both the relationship linking the deceased and the cause of their simultaneous death. During the Merovingian period in Northeast France, multiple burials were revealed as highly rare and were consequently considered special burials linked to exceptional dramatic events. To help document the status of the deceased recovered from such special burials, we conducted ancient DNA analyses (mitochondrial and nuclear markers) to investigate the possible maternal kinship between a woman and three immature individuals simultaneously deposited in burial 41 at the Hérange site (Lorraine, France). The genetic data obtained (i) strongly supported a maternal (genetic) kinship between the woman centrally deposited in the burial and the two immatures deposited right beside her but (ii) permitted the exclusion of a genetic link between the woman and the teenager deposited along her legs. Thus, these data support the view that survivors had intimate knowledge of the deceased relationship and buried these individuals in a manner to illustrate their biological connections. As a consequence, if a common cause of death was the presupposition for the special treatment of the deceased recovered from Hérange burial 41, then interpersonal relationship was likely the deciding factor for setting this multiple burial. Graphical abstract: Unlabelled Image Highlights: Multiple burials are rare during the Merovingian period in Northeast France. The relationship linking the deceased recovered in such burials remains unknown. Ancient DNA analyses permit to demonstrate maternal links in Hérange burial 41. The arrangement of the deceased in the burial mirrors their relations in life. Interpersonal relationship was likely the deciding factor for setting this burial.